Conhecimento de graduandos em enfermagem e enfermeiros sobre o programa de gerenciamento de antimicrobianos (PGA): construção e validação de instrumento - Simões, Lilian Isabel (2022)
Antimicrobials (ATM), a class of medicines that save countless lives, over the years have started to be used on a large scale and often in an indiscriminate and unnecessary way, contributing to microbial resistance (MR) and becoming a serious health problem. global health. One of the strategies developed to combat MR was the creation of the Antimicrobial Management Program (PGA), emphasizing the improvement of control mechanisms for the use of ATM. The inclusion of nurses in a clear, articulated way and with well-defined functions is still incipient in the PGA, pointing to more specific training and training needs on the subject for these professionals. The production of measurement instruments that collaborate with this process is essential. Objective: Develop and validate an instrument to measure the knowledge of nursing students and nurses about the PGA. Method: Methodological study with a quantitative approach. The instrument was developed based on international consensus guidelines, organized into four domains: infection prevention and control; diagnosis of infection and use of antimicrobials; clinical practice of nurses and person-centered care and interprofessional practice on the topic.Content validation was carried out by twelve expert judges who analyzed the instrument for clarity and relevance, using a 4-point Likert scale. Items with a content validity index ≥ 0.80 were considered valid. To evaluate each domain, an agreement rate above 80% was considered adequate. After this stage, the pre-test was carried out with 31 nursing students and nurses. Results: The initial instrument contained 31 questions and upon validation by judges, 12 items underwent wording changes, one item was added (domain 1), one item was unified (domain 2) and two items were deleted (domain 3 and 4). In the pre-test, seven items were rewritten in order to facilitate understanding and not be a confusing factor. The final instrument consisted of 30 dichotomous questions. Conclusion: The tool developed was validated and is available for use in different health care scenarios, being able to measure knowledge prior to and subsequent to educational interventions, being highly effective for use in training students and updating nurses on the topic. Keywords: Surveys and questionnaires; antimicrobial management; nurses and nurses; nursing students; infection control; validation study